Ruminal kinetics of the degradation oat-potato foliage silage containing wheat bran in Brown Swiss cattle - Carrasco Sanchez, Deice (2022)
The aim of this study was to evaluate the ruminal kinetics of the degradation of dry matter (DM), crude protein (CP) and neutral detergent fibre (NDF) of oat silage - potato foliage, in the ratio of 70:30, including four levels of wheat bran (0, 10, 20, 30%, based on the natural matter of the ensiled mass). A factorial randomized block design of 4 x 6 (levels, times) with three replications was used. Three Brown Swiss cattle with ruminal fistula were used. Samples (5 g) were placed in a nylon bag and incubated for 4, 8, 12, 24, 48 and 72 h. Zero time (t0) was used to calculate the soluble fraction. The disappearance (degradability) of DM, CP and NDF showed a quadratic result, observing an increase in the degradability of these nutrients up to the optimum level of 27.64, 22.64 and 27.80% inclusion of wheat bran in oat silage - potato foliage for 48 h of incubation, respectively. Except for DM, the potential and effective degradability at flow rates of 2, 5 and 8%/h of the CP and NDF of the silages were influenced by the levels of wheat bran. In the silages with 10, 20 and 30% wheat bran, the potential degradability of NDF ranged from 74.99 to 84.36%. Wheat bran, at the levels studied, improved the constant rate (c) of potential and effective degradability of the DM, CP and NDF of the silages, which were characterized as feeds of high nutritional quality.